(untitled) (Research, Society and Development, 2021)
This study aims to analyze the number of active cargo transport companies in Brazil, comparing the growth in the number of companies in different regions of the country. The research is descriptive and exploratory, with data on the number of active cargo transport companies in Brazil obtained from the Map of Companies Panel, under the responsibility of the Federal Government. It was found that the country showed a significant growth in the number of active companies between the years 2010 to 2021, with the South region showing the greatest growth, followed by the South, Northeast, Midwest and North regions, respectively. Cargo transport companies by road modal represent the largest number of active transport logistics companies, reinforcing that the Brazilian transport matrix is ​​based on this modal. The inexpressive number of companies operating in other modes stands out compared to road transport, highlighting the need to expand these modes, in order to facilitate integration among all.